I See My Future!: Linking Mentoring, Future Work Selves, Achievement Orientation to Job Search Behaviors - Kao, Kuo-Yang; Hsu, Hao-Hsin; Rogers, Altovise; Lin, Mi-Ting; Lee, Hui-Ting; Lian, Ruirui (Journal of career development, 2022)
Mentoring is related to young adults’ career planning. The present study attempts to examine whether the perception of future work selves could be a critical mediating mechanism underlying the relationship between the reception of mentoring functions and job search behaviors. Moreover, we also investigated the moderating role of achievement orientation on this relationship. We tested our hypotheses with a time-lagged research design. Results indicated that psychosocial mentoring was related to future work selves, and future work selves were associated with job search behaviors. Future work selves mediated the relationship between psychosocial mentoring and job search behaviors. Moreover, achievement orientation moderated the direct and indirect effects of psychosocial function on job search behaviors. Specifically, the aforementioned relationships were stronger when achievement orientation was high compared to when achievement orientation was low. Important theoretical and practical implications for mentoring and career research are discussed in the current study.